High-throughput targeted long-read single cell sequencing reveals the clonal and transcriptional landscape of lymphocytes - Mandeep Singh (Nature Portfolio, 2019)
Single cell RNA sequencing generates short reads from one end of a template, providing incomplete transcript coverage and limiting identification of diverse sequences such as antigen receptors. Here the authors combine long read nanopore sequencing with short read profiling of barcoded libraries to generate full-length antigen receptor sequences.